2020
DOI: 10.1044/2020_persp-20-00078
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current Approaches to Aural Rehabilitation for Adults With Cochlear Implants

Abstract: Purpose This clinical focus article provides an overview of clinical models currently being used for the provision of comprehensive aural rehabilitation (AR) for adults with cochlear implants (CIs) in the Unites States. Method Clinical AR models utilized by hearing health care providers from nine clinics across the United States were discussed with regard to interprofessional AR practice patterns in the adult CI population. The clinical models were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Existing evidence supports the benefits of AR on the auditory experience for adult CI recipients (e.g., Cohen et al, 2004;Dubno, 2013;Hawkins, 2005;Hawthorne et al, 2004;Olson, 2015), and several sources provide insights on best practices for AR (e.g., Ferguson et al, 2019;Glade et al, 2020;Sweetow & Palmer, 2005). However, few peer-reviewed articles describe the process of creating and implementing an audiologist-led teleaudiology AR program for adult CI recipients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing evidence supports the benefits of AR on the auditory experience for adult CI recipients (e.g., Cohen et al, 2004;Dubno, 2013;Hawkins, 2005;Hawthorne et al, 2004;Olson, 2015), and several sources provide insights on best practices for AR (e.g., Ferguson et al, 2019;Glade et al, 2020;Sweetow & Palmer, 2005). However, few peer-reviewed articles describe the process of creating and implementing an audiologist-led teleaudiology AR program for adult CI recipients.…”
Section: Discussionmentioning
confidence: 99%
“…While the four pillars of a comprehensive AR program are well described (i.e., Boothroyd, 2007;Ferguson et al, 2019;Sweetow & Palmer, 2005), it is up to AR providers to select appropriate tools and format for their program. Glade et al (2020) conducted a focus group of comprehensive AR providers for adult CI recipients at nine clinical sites across the United States. Findings revealed that while all sites employed the four pillars of an effective AR program (sensory management, instruction, counseling, and perceptual training), they employed a variety of service delivery models.…”
Section: Essential Components Of An Ar Programmentioning
confidence: 99%
See 3 more Smart Citations